Analysis of steel structure for 5-stories apartment using ANSYS - Ooi, Yoong Kam (2019)
In this research, a 3D steel frame was analyzed by manual calculation and also ANSYS program with the probabilistic method. This analysis is to determine the stress, strain, deflection and deformation of the structure. Besides that, the structure is checked accordingly to Eurocode 3 also. Nowadays steel frame is widely used for industrial building. It is very stable in term of everything and low in cost. A 500N/mm2 of yield strength was choose for the 3D steel frame. The material and geometry of the space truss was satisfied for this research since it passed all the design criteria in designing for tensile, compression and also buckling. The numerical results show very good agreement with manual calculation results. From the results of simulation, we get to know the real behavior of the structure under the applied loads. In probabilistic analysis, we get the results of cumulative distribution function, histogram plot, sensitivity plot and simple history plot by 10000 times of simulation for any input and output.